Thermal analysis of a solar latent heat storage system using Scheffler concentrator for agricultural applications. (5th January 2023) - Munir, Zeeshan; Roman, Franz; Niazi, Badar Munir Khan; Mahmood, Naveed; Munir, Anjum; Hensel, Oliver
Highlights: Use of PCM in Agriculture processes is very limited despite great potential. A novel latent heat storage unit is developed to accommodate multiple agriculture processes. Solar irradiance intensity and inlet temperature dictate the charging performance. The system in standalone operation can pasteurize 5kg of milk . Abstract: Latent heat thermal storage (LHTS) using phase change materials (PCMs) has been successfully adapted in various fields but its use in agriculture has remained very limited mainly involving solar dryers and greenhouses. This study aims to develop a standalone application flexible LHTS system capable of storing and supplying solar thermal energy to various suitable agricultural processes under 100 °C. The system consisted of a 2.5 m 2 laying type Scheffler concentrator, a heat receiver, a PCM tank, and an oil tank. The system was subject to various flow rates and solar irradiance to evaluate its performance as a thermal backup for milk pasteurization. During charging, the heat receiver showed a 67.9 % improvement in thermal efficiency while the PCM tank registered a 16.7 % decline against an increase in flow rate from 2.5 LPM to 15 LPM. The liquefaction rate of the PCM was noticeably influenced by the HTF inlet temperature rise as the melting time under 1.14 °C was 95 min followed by 108 min, 113 min, and 117 min against temperature rise of 1.05 °C, 0.88 °C, and 0.86 °C respectively. The total heat content of the PCM tank against various flow rates varied from 1.07 kWh to 1.14 kWh. During discharging, the rate of heat extraction was strongly influenced by the thermal gradient between the HTF and the PCM resulting in a 1.26 times higher PCM tank efficiency compared to charging. The latent heat released by the PCM was enough to theoretically pasteurize 5 kg of raw milk in a setup having 50 % heat transfer efficiency.